Sultan Sumbawa Political Communication Pattern in Managing the Government (Study of Sultan Kaharuddin III's Government) - Ofi Hidayat (GoAcademica Research & Publishing, 2020)
The role of political communication in running a government is a way to achieve a goal. Political communication in Indonesia has existed since the time of the ancient Javanese kingdom. The study of political communication in Asia, especially in Indonesia, is still not too famous as in Western countries, the study of political correspondence that develops in Indonesia has more to do with modern governance based on the concept of Western political studies. In this study, researchers will examine what forms of social-political communication exist in Indonesia, especially in the former Sultanate. The government of Sultan Kaharuddin III, who led the Sultanate of Sumbawa, was chosen as the object of study this time. This research was conducted because during the reign of Sultan Sumbawa, when it used a government system that adopted Islamic values ​​and at that time also was a transition period for the independence of the Republic of Indonesia, then the Sultanate of Sumbawa only joined the Republic of Indonesia in 1950. This research will be examined using qualitative research methods. Researchers will look for how the form of political communication by Sultan Sumbawa using data collection techniques by observation, interviews with informants, and other supporting data collection. Researchers will interpret the phenomena that occur by using phenomenology. The results of this study describe the form of Sultan Sumbawa's political communication that uses the noble values ​​of social philosophy and is based on Islamic values ​​in running the government. The use of local arts and traditions has also become one of the political communication media used to achieve goals in the government system. So this is a distinguishing factor between the Sumbawa Sultanate and other Sultanates in Indonesia.